(untitled) (Advances in Oceanography and Limnology, 2011)
For the first time the structure of the anchovy stock was investigated in the Strait of Sicily: sampling locations were in Sicily, in Tunisia and in the Adriatic Sea. A morphological approach to stock discrimination which involves morphometric landmarks analysis was adopted. The aim of this work is to describe any morphological variations between the samples areas and individuate possible different populations in order to obtain useful information for management of shared resources between Tunisian and Italian waters. Furthermore sexual dimorphism was investigated. Results of morphometric landmarks may suggest a high level of overlapping among Sicily and Tunisia. Instead, between the Sicilian and Adriatic population, it was observed a certain degree of isolation, suggesting the existence of two anchovy sub-populations connected by a possible migration of a small number of individuals. No differences between male and female individuals was observed. Results support the likely existence of an anchovy metapopulation with several sub-populations, one inhabiting the northern and southern parts of the Strait of Sicily. From a management perspective and under the ‘precautionary approach’, these sub-populations should be treated as shared stocks and conserved.